2022
DOI: 10.1021/acsomega.2c06568
|View full text |Cite
|
Sign up to set email alerts
|

Combined Heterogeneous Catalyst Based on Titanium Oxide for Highly Efficient Oxidative Desulfurization of Model Fuels

Abstract: In this work, new heterogeneous Mo-containing catalysts based on sulfonic titanium dioxide were developed for the oxidation of sulfur-containing model feed. The synergistic effect of molybdenum and sulfonic group modifiers allows for enhancing catalytic activity in dibenzothiophene oxidative transformation, and a strong interaction between support and active component for thus obtained catalysts provides increased stability for leaching. For the selected optimal conditions, the Mo/TiO2-SO3H catalyst exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…As the temperature decreases, a rather sharp drop in DBT conversion occurs (in the presence of both catalysts). This is due to two main factors (Figure C): the first is due to the fact that active peracids are intensively formed under the influence of hydrogen peroxide only at elevated temperatures . The second factor is associated with the adsorption of water and hydrogen peroxide on the acid sites of the catalyst–the higher the temperature, the more intense the desorption of water and hydrogen peroxide, the easier the diffusion of nonpolar DBT into the pores of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the temperature decreases, a rather sharp drop in DBT conversion occurs (in the presence of both catalysts). This is due to two main factors (Figure C): the first is due to the fact that active peracids are intensively formed under the influence of hydrogen peroxide only at elevated temperatures . The second factor is associated with the adsorption of water and hydrogen peroxide on the acid sites of the catalyst–the higher the temperature, the more intense the desorption of water and hydrogen peroxide, the easier the diffusion of nonpolar DBT into the pores of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown the combination of two types of active centers: Bronsted acid sites and molybdenum compounds have a synergistic effect and can significantly reduce the reaction time. , Thus, the combination of immobilized nicotinic acid with phosphomolybdic acid anchored on SBA-15 allows the complete oxidation of DBT to the corresponding sulfone in just 5 min . The multifunctional role of nicotinic acid has been shown: the carboxylic group is responsible for coordinating the sulfur-containing substrates and the formation of the corresponding peracid.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified five distinct groups of heterogeneous catalysts used in the ODS process: transition metal oxides stabilized, polyoxometalates, ionic liquids, , carbon materials, and porous materials . Transition metal heterogeneous catalysts have drawn significant attention as a result of their suitable Lewis acid sites and excellent catalytic performance in the ODS process. , …”
Section: Influence Of Reaction Factors On Odsmentioning
confidence: 99%
“…38 Transition metal heterogeneous catalysts have drawn significant attention as a result of their suitable Lewis acid sites and excellent catalytic performance in the ODS process. 39,40 3.1.1. Transition Metal Oxides.…”
Section: Influence Of Reaction Factors On Odsmentioning
confidence: 99%
“…The major content of the sulfur compounds (such as thiols, sulfides, and disulfides) is removed by HDS technology; however, some refractory sulfur compounds, such as dibenzothiophene (DBT) and its alkylated derivatives, cannot be easily removed by conventional HDS . In order to remove the HDS refractory sulfur compounds effectively, non-HDS methods such as adsorption, oxidation, biodesulfurization, and extractive desulfurization (EDS) have been investigated. , Extractive desulfurization (EDS) is an attractive non-HDS method due to its high capability in the removal of refractory sulfur compounds, its simplicity, and its low energy consumption due to mild operating conditions compared to HDS technology …”
Section: Introductionmentioning
confidence: 99%